The Innovation and the Transformation of Indonesian Schools Accreditation Management System - Budi Susetyo; Sylvia P. Soetantyo; Muhammad Sayuti; Darfiana Nur (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
All schools at the primary and secondary education levels in Indonesia must be accredited. An independent body called the National Accreditation Board for Schools/Madrasah (BAN-S/M) as an external quality assurance agency, accredits schools throughout Indonesia. Since 2005, the percentage of schools accredited in levels A and B has always increased from year to year based on the accreditation results. However, the improvement of school quality based on accreditation did not strongly correlate with the national exam and PISA results. This article discusses the facts of the experience of implementing accreditation for 15 years which became the basis for accreditation reform in Indonesia. BAN-S/M started the reformation in 2020 with three fundamental changes. First, the change in the accreditation instrument from compliance-based to performance-based. Second, the recruitment of new assessors based on cognitive competence and personality. Third, the changes of the accreditation business process through the dashboard monitoring system that will select schools with automatic accreditation extensions without visitation and schools that assessors must visit. implementation of Innovation and accreditation management reform can reduce accreditation costs by more than 60% and is expected to increase the accuracy of school quality assessment results. The findings strengthen the current transformation to the new, more efficient, rational accreditiation management system for schools/madrasah.